TINDAK MENGANCAM MUKA NEGATIF UNGKAPAN PENOLAKANDI KALANGAN KOMUNITAS WAHANA TRI TUNGGAL (WTT) TERHADAP PEMBANGUNAN BANDARA DI KULONPROGO: KAJIAN PRAGMATIK - Faizah, Naimul; , Prof. Dr. Markhamah (2015)
This research have purpose to: (1) to identify the threaten action of nefative face in Wahana Tri Tunggal circle community; and (2) to identify the scale of politeness in Wahana Tri Tunggal circle community. The kind of this research is qualitative descriptive. This research implemented since November 2014 until April 2015. The location of research is in Glagah Village, Kulonprogo, DIY. The object of the reseacrh is threaten action of negative face and politeness scale that collected from documentation technique and analysize using padan referensial methods dan padan pragmatis methods. The results of research are: first, the threaten action of negative face are: 1 anger expression as many as 16 datas; 2) prohibit as many as 11 datas; 3) warning as many as 9 datas; 4) asking as many as 5 data; 5) threating as many as 5 data; 6) command as many as 3 data; and 7) challenge as many as 1 data. Second, politeness scale which is formed refusing of WTT on the building of airport are: 1) indirectness scale with direct speech as many as 26 datas; 2) social distance scale is find 11 datas; there are far social space as many as 7 datas, medium social space as many as 1 data, and close social space as many as 3 datas; 3) cost benefit scale as many as 8 datas; 4) authority scale that find as many as 4 datas, that are using greeting form with the rank politeness as many as 3 datas and without greeting form with impoliteness as many as 1 data; and 5) optionality scale with two answer choices as many as 1 data. Third, the form of these refuse is unacceptability expression of citizen (aspecially WTT comunity) in planning of the building of new airport in Kulonprogo which is there are many use from the field of citizen.